The Case of the Secret Code B.2 - Thomas, Jerry D.; Nang Chan Yeema (Nampa, ID USA Pacific Press Publishing Association, 1995)
When Willie, confined to a wheelchair, receives coded messages signed "G.O.D." on his computer, he needs the help of other Shoebox Kids, as well as prayer, to identify the writer and find Willie's missing dog.
Keywords: Story Collection